2005
DOI: 10.1021/je050241s
|View full text |Cite
|
Sign up to set email alerts
|

Infinite Dilute Activity and Diffusion Coefficients in Polymers by Inverse Gas Chromatography

Abstract: The infinite dilute activity and diffusion coefficients of solvents in poly(vinyl alcohol) and cross-linked poly(vinyl alcohol) are determined by using inverse gas chromatography technique with a packed column. Experimental results for water, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 1-pentanol, and 3-methyl-1-butanol in poly(vinyl alcohol); for water, methanol, and ethanol in cross-linked poly(vinyl alcohol) at different temperatures are presented. The van Deemter equation is used to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…Figure 1 is a schematic of the IGC unit. 21 Nitrogen was used as the carrier gas and a small pulse of the solvent (0.1 lL) was injected into the column using a 0.5 lL syringe. The carrier gas flowed directly to the column which was enclosed in the temperature controlled oven.…”
Section: Igc Measurementsmentioning
confidence: 99%
“…Figure 1 is a schematic of the IGC unit. 21 Nitrogen was used as the carrier gas and a small pulse of the solvent (0.1 lL) was injected into the column using a 0.5 lL syringe. The carrier gas flowed directly to the column which was enclosed in the temperature controlled oven.…”
Section: Igc Measurementsmentioning
confidence: 99%
“…Among all these techniques, inverse gas chromatography (IGC) is one of the most widely used, because it gives a great deal of information with relatively simple measurements. In literature, this technique has been used with many different polymeric materials, always with good results 16, 17. Another important point is that it has been demonstrated that the obtained values with this technique (at solvent infinite dilution conditions) can be extrapolated to the overall composition range 18…”
Section: Introductionmentioning
confidence: 95%
“…Inverse gas chromatography (IGC) is a simple, fast, reliable and powerful tool for the investigation of the sorption and diffusion behavior of small molecules in polymers. [21][22][23] This method can be used to determine the main sorption thermodynamic parameters of polymer-solvent systems, such as, activity coefficient, solubility coefficient, the Flory-Huggins interaction parameter and solubility parameter, partial molar excess free energy of mixture and enthalpy of sorption. [24][25][26][27][28] The infinite dilution diffusion coefficients of solvent and no-solvent in polymer can be measured exactly.…”
Section: Introductionmentioning
confidence: 99%